Respuesta :
Answer:
Option b 18x-8 is correct answer.
Step-by-step explanation:
We need to simplify the expression 4(3x – 2) + 6x(2 – 1) and find the result.
Solving:
= 4(3x – 2) + 6x(2 – 1)
Multiplying terms with values in the bracket.
= 12x - 8 + 12x -6x
Adding like terms
= 12x + 12x - 6x -8
= 24x -6x -8
= 18x -8
So, Option b 18x-8 is correct answer.
You simplify expressions by distributing where possible and combining like terms where possible.
4(3x - 2) + 6x(2 - 1)
12x - 8 + 12x - 6x <--- Used the distributive property for both parentheses.
18x - 8 <--- Combined like terms.
So, B. 18x - 8 is the answer.